Electrochemical Determination of Tetracycline at SPCE modified with Nanocomposite - Sundus H. Merza (Journal of Global Pharma Technology, 2018)
An electrochemical sensor based on manganese dioxide nanorodMnO2and Graphene oxide (GO) functionalized with 4-amino, 3-substituted 1H, 1, 2, 4 Triazole 5(4H) thion (FGO)/MnO2Nanocompositewas developed for voltammetric determination of Tetracycline (TET).The working electrode WE of SPCE was modified bya drop casting method. X-ray powder diffractometer (XRD), scanning electron microscopy (SEM) and FT-IR were employed to characterize the synthesized FGO/MnO2. The determination of TET at the modified electrode was studied by cyclic voltammetry (CV) and differential pulse voltammetry (DPV) in the phosphate buffer solution (PBS).TET show sharp increase in the oxidation peaks in the pH 2.Voltammetric characteristics of TET (Epa, Ipa) were estimated. From effect of scan rate, the average surface coverage ( ) of TET on the surface of SPCE modified with FGO/MnO2 nanocomposite, the electron transfer coefficient and electron transfer constant rate ket was obtained as 10.56×1014 molecule cm-2, 0.5, and 10.41 cm.s-1respectively. Under the optimal conditions, the peak current shows linear relationship with concentration of Tetracycline (TET) ranges 1–9 µM with the detection limit of 0.2 M. The modified SPCE was successfully used to detect TETKeywords: SPCE, Functionalize graphene oxide, Cyclic voltammetry.